Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the solutions to the quadratic equation [tex]\( 6 = x^2 - 10x \)[/tex], let's follow these steps:
1. Rewrite the Equation in Standard Form:
A quadratic equation in standard form is [tex]\( ax^2 + bx + c = 0 \)[/tex].
The given equation:
[tex]\[ 6 = x^2 - 10x \][/tex]
can be rewritten as:
[tex]\[ x^2 - 10x - 6 = 0 \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -10 \)[/tex], and [tex]\( c = -6 \)[/tex].
2. Identify the Coefficients:
From the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], identify the coefficients:
[tex]\[ a = 1,\quad b = -10,\quad c = -6 \][/tex]
3. Use the Quadratic Formula:
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Plug in the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4 \cdot 1 \cdot (-6)}}{2 \cdot 1} \][/tex]
4. Simplify Inside the Square Root:
Calculate the discriminant [tex]\( b^2 - 4ac \)[/tex]:
[tex]\[ b^2 = (-10)^2 = 100 \][/tex]
[tex]\[ 4ac = 4 \cdot 1 \cdot (-6) = -24 \][/tex]
[tex]\[ b^2 - 4ac = 100 - (-24) = 100 + 24 = 124 \][/tex]
5. Substitute Back into the Formula:
So the formula becomes:
[tex]\[ x = \frac{10 \pm \sqrt{124}}{2} \][/tex]
6. Simplify the Radical:
Express [tex]\( \sqrt{124} \)[/tex] in simplest radical form:
[tex]\[ \sqrt{124} = \sqrt{4 \cdot 31} = 2\sqrt{31} \][/tex]
Thus, the equation simplifies to:
[tex]\[ x = \frac{10 \pm 2\sqrt{31}}{2} \][/tex]
7. Simplify the Fraction:
Divide both terms in the numerator by 2:
[tex]\[ x = 5 \pm \sqrt{31} \][/tex]
Therefore, the solutions in simplest radical form are:
[tex]\[ x = 5 + \sqrt{31} \quad \text{and} \quad x = 5 - \sqrt{31} \][/tex]
1. Rewrite the Equation in Standard Form:
A quadratic equation in standard form is [tex]\( ax^2 + bx + c = 0 \)[/tex].
The given equation:
[tex]\[ 6 = x^2 - 10x \][/tex]
can be rewritten as:
[tex]\[ x^2 - 10x - 6 = 0 \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -10 \)[/tex], and [tex]\( c = -6 \)[/tex].
2. Identify the Coefficients:
From the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex], identify the coefficients:
[tex]\[ a = 1,\quad b = -10,\quad c = -6 \][/tex]
3. Use the Quadratic Formula:
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Plug in the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4 \cdot 1 \cdot (-6)}}{2 \cdot 1} \][/tex]
4. Simplify Inside the Square Root:
Calculate the discriminant [tex]\( b^2 - 4ac \)[/tex]:
[tex]\[ b^2 = (-10)^2 = 100 \][/tex]
[tex]\[ 4ac = 4 \cdot 1 \cdot (-6) = -24 \][/tex]
[tex]\[ b^2 - 4ac = 100 - (-24) = 100 + 24 = 124 \][/tex]
5. Substitute Back into the Formula:
So the formula becomes:
[tex]\[ x = \frac{10 \pm \sqrt{124}}{2} \][/tex]
6. Simplify the Radical:
Express [tex]\( \sqrt{124} \)[/tex] in simplest radical form:
[tex]\[ \sqrt{124} = \sqrt{4 \cdot 31} = 2\sqrt{31} \][/tex]
Thus, the equation simplifies to:
[tex]\[ x = \frac{10 \pm 2\sqrt{31}}{2} \][/tex]
7. Simplify the Fraction:
Divide both terms in the numerator by 2:
[tex]\[ x = 5 \pm \sqrt{31} \][/tex]
Therefore, the solutions in simplest radical form are:
[tex]\[ x = 5 + \sqrt{31} \quad \text{and} \quad x = 5 - \sqrt{31} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.